The Problem of Orphan Works in the EU. An overview of legislative solutions and main actions in this field - Vetulani, Agnieszka (My University, 2008)
Digital and web-based information technology and media give the public new possibilities of exploiting cultural material. Works existing in analogue form can now be easily digitised and therefore reused for different purposes and by different users. Both industries and cultural institutions are taking advantage of the new opportunities opened up by digital technology. In the case of the activities carried out by cultural institutions, the purpose of digitisation is often not only to preserve cultural and scientific material but also to provide users with access to their resources, including access online. However, before digitising and further reutilising material that is still in copyright, the prospective user must often obtain consent from the copyright owner. The problem appears when it is impossible to find or locate right holders or when right holders remain unknown. This is the problem of so called ‘orphan works’. Without a suitable permission from the owner, digitisation and further exploitation of the material might not take place. Such a situation is to the detriment not only of the user, but often of the public, as no-one profits from cultural material left unexploited due to its orphan status. To promote digitisation, online accessibility and preservation of digital material of cultural institutions, the European Commission launched the "i2010: Digital Libraries" programme in September 2005. Discussions on how to deal with orphan works are currently being undertaken by stakeholders and cultural and collective management institutions at different levels and scopes. Some of them have been initiated by the stakeholders themselves, others by the European Commission or by Member States. The aim of these discussions is to find a solution to facilitate the use of orphan material without prejudice to copyright. The potential solution should provide legal certainty both to users and right holders, should the right holders reappear after the use of orphan works was made without their explicit consent. The objective of this report is to give a general overview of the situation of orphan works in the European Union. The report describes possible legislative solutions to the issue, as well as main actions that are currently underway in this field. Chapter I presents the nature and scope of the problem and describes existing and proposed legislative solutions both in Europe and abroad. It also focuses on the key issues, underlining the cross-border nature of the problem. Chapter II concerns actions undertaken by the European Commission in relation to the issue of orphan works. Firstly, it summarises the Commission Recommendation and Council conclusions on digitisation and online accessibility in relation to the orphan works’ issue. Secondly, it presents the work of the High Level Expert Group on Digital Libraries and its subgroup dealing with copyright related issues within the digital libraries framework. Finally, it describes ongoing actions undertaken by institutions and stakeholders at the initiative of the European Commission. Chapter III presents voluntary actions undertaken independently by some institutions and stakeholders. It describes current practices of institutions and mechanisms that are already working in practice, then, solutions supported by different stakeholders are presented, and finally, it gives examples of more recent actions undertaken by institutions and stakeholders at their own initiative that are still under way. Chapter IV is about the approach of Member States to the orphan works problem. This chapter presents actions, if any, that have been undertaken by Member States in order to introduce mechanisms or measures to facilitate the exploitation of orphan works in their respective countries in response to the Commission Recommendation and Council conclusions. The last part of the report contains a set of conclusions that can be drawn at this stage and possible follow-up on this issue.
Keywords: orphan works; copyright; European Commission; policy-making